Opposite Effects of Glucagon and Insulin on Compensation for Spectacle Lenses in Chicks - Zhu, Xiaoying (2008)
PURPOSE: Chick eyes compensate for defocus imposed by positive or negative spectacle lenses. Glucagon may signal the sign of defocus. Do insulin (or IGF-1) and glucagon act oppositely in controlling eye growth, as they do in metabolic pathways and in control of retinal neurogenesis? METHODS: Chicks, wearing either lenses or diffusers or neither over both eyes, were injected with glucagon, a glucagon antagonist, insulin, or IGF-1 in one eye (saline in other eye). Alternatively, chicks without lenses received insulin plus glucagon in one eye, and either glucagon or insulin in the fellow eye. Ocular dimensions, refractive errors and glycosaminoglycan synthesis were measured over 2-4 days. RESULTS: Glucagon attenuated the myopic response to negative lenses or diffusers by slowing ocular elongation and thickening the choroid; in contrast, with positive lenses, it increased ocular elongation to normal levels and reduced choroidal thickening, as did a glucagon antagonist. Insulin prevented the hyperopic response to positive lenses by speeding ocular elongation and thinning the choroid. In eyes without lenses, both insulin and IGF-1 speeded, and glucagon slowed, ocular elongation, but either glucagon or insulin increased the rate of thickening of the crystalline lens. When injected together, insulin blocked choroidal thickening by glucagon, at a dose that did not, by itself, thin the choroid. CONCLUSIONS: Glucagon and insulin (or IGF-1) cause generally opposite modulations of eye-growth, with glucagon mostly increasing choroidal thickness and insulin mostly increasing ocular elongation. These effects are mutually inhibitory and depend on the visual input.